2008
DOI: 10.1038/oby.2007.129
|View full text |Cite
|
Sign up to set email alerts
|

Meal‐related Changes in Ghrelin, Peptide YY, and Appetite in Normal Weight and Overweight Children

Abstract: objective: Ghrelin and peptide YY (PYY) are two gut hormones that have effects on appetite. Our objectives were to characterize the patterns of secretion of these hormones in response to feeding in school-age children and determine whether there were differences between normal weight (NW) and overweight (OW) subjects. Methods and Procedures: This was a cross-sectional study at one tertiary care center. Subjects were 7-to 11-year-old healthy NW and OW volunteers recruited from local advertisements. Following an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 33 publications
8
46
5
1
Order By: Relevance
“…Our results suggest that a high-protein breakfast for as short as 3 months can promote a better weight loss effect in obese Chinese adolescents. This is consistent with the results of other clinical studies in children in the USA [30,31]. This is very exciting as it may point out a direction for intervention of childhood obesity in our daily clinical practice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results suggest that a high-protein breakfast for as short as 3 months can promote a better weight loss effect in obese Chinese adolescents. This is consistent with the results of other clinical studies in children in the USA [30,31]. This is very exciting as it may point out a direction for intervention of childhood obesity in our daily clinical practice.…”
Section: Discussionsupporting
confidence: 81%
“…Some showed that ghrelin did not respond to a meal [31], while others suggested that the pattern of ghrelin is similar to that in adults with a reduction after a meal [38,39,40]. A recent study in obese prepubertal children suggested that ghrelin reduces more significantly in a high-protein diet compared with a high-carbohydrate diet, which seems be associated with increased satiety [31]. The correlation between ghrelin, satiety and weight loss may indicate the orexigenic role of ghrelin in weight loss [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…These discrepant findings probably reflect the marked variability in fasting plasma ghrelin concentrations, which has also been reported in other studies, in which PWS children were compared to age-matched controls 23,30,31). Notably, in the work by Haqq et al (20), only one-third of PWS children were hyperghrelinemic, a finding in clear contrast with the prevailing detection of high ghrelin levels in PWS adults (21,22).…”
Section: Discussioncontrasting
confidence: 53%
“…While these results are in agreement with the results provided by Coelho et al (2006), they differ from those reported by Lomenick et al (2008), which found no difference in subjective appetite response between lean and overweight participants. The inconsistency may be because the intervention period in those studies was different (3 h versus 8 h).…”
Section: Discussioncontrasting
confidence: 67%
“…While this makes the results more generalizable to a wider population, it may also mask potential different responses between lean and overweight participants. To date, only a limited number of studies have investigated the difference in appetite responses between overweight and lean participants; the results remain inconclusive (Brondel et al, 2007;Coelho et al, 2006;Lomenick et al, 2008;Seimon et al, 2013). Different study design, test foods and study populations may have partly accounted for the conflicting results.…”
Section: Introductionmentioning
confidence: 87%